Cerebellum and cognition in Friedreich ataxia: a voxel-based morphometry and volumetric MRI study - Cocozza, Sirio; Costabile, Teresa; Pontillo, Giuseppe; Lieto, Maria; Russo, Camilla; Radice, Leonardo; Pane, Chiara; Filla, Alessandro; Brunetti, Arturo; Saccà, Francesco (Journal of neurology, 2020)
Background Recent studies have suggested the presence of a significant atrophy affecting the cerebellar cortex in Friedreich ataxia (FRDA) patients, an area of the brain long considered to be relatively spared by neurodegenerative phenomena. Cognitive deficits, which occur in FRDA patients, have been associated with cerebellar volume loss in other conditions. The aim of this study was to investigate the correlation between cerebellar volume and cognition in FRDA. Methods Nineteen FRDA patients and 20 healthy controls (HC) were included in this study and evaluated via a neuropsychological examination. Cerebellar global and lobular volumes were computed using the Spatially Unbiased Infratentorial Toolbox (SUIT). Furthermore, a cerebellar voxel-based morphometry (VBM) analysis was also carried out. Correlations between MRI metrics and clinical data were tested via partial correlation analysis. Results FRDA patients showed a significant reduction of the total cerebellar volume ( p = 0.004), significantly affecting the Lobule IX ( p = 0.001). At the VBM analysis, we found a cluster of significant reduced GM density encompassing the entire lobule IX ( p = 0.003). When correlations were probed, we found a direct correlation between Lobule IX volume and impaired visuo-spatial functions ( r = 0.58, p = 0.02), with a similar correlation that was found between the same altered function and results obtained at the VBM ( r = 0.52; p = 0.03). Conclusions With two different image analysis techniques, we confirmed the presence of cerebellar volume loss in FRDA, mainly affecting the posterior lobe. In particular, Lobule IX atrophy correlated with worse visuo-spatial abilities, further expanding our knowledge about the physiopathology of cognitive impairment in FRDA.